Identification and Expression Profile of CLE41/44-PXY-WOX Genes in Adult Trees Pinus sylvestris L. Trunk Tissues during Cambial Activity - Natalia A. Galibina; Yulia L. Moshchenskaya; Tatiana V. Tarelkina; Kseniya M. Nikerova; Maxim A. Korzhenevskii; Aleksandra A. Serkova; Nikita V. Afoshin; Ludmila I. Semenova; Diana S. Ivanova; Elena N. Guljaeva; Olga V. Chirva (Plants, 2023)
WUSCHEL (WUS)-related homeobox (WOX) protein family members play important roles in the maintenance and proliferation of the stem cells in the cambium, the lateral meristem that forms all the wood structural elements. Most studies have examined the function of these genes in angiosperms, and very little was known about coniferous trees. Pine is one of the most critical forest-forming conifers globally, and in this research, we studied the distribution of WOX4, WOX13, and WOXG genes expression in Pinus sylvestris L. trunk tissues. Further, we considered the role of TDIF(CLE41/44)/TDR(PXY) signaling in regulating Scots pine cambial activity. The distribution of CLE41/44-PXY-WOXs gene expression in Scots pine trunk tissues was studied: (1) depending on the stage of ontogenesis (the first group of objects); and (2) depending on the stage of cambial growth (the second group of objects). The first group of objects is lingonberry pine forests of different ages (30-, 80-, and 180-year-old stands) in the middle taiga subzone. At the time of selection, all the trees of the studied groups were at the same seasonal stage of development: the formation of late phloem and early xylem was occurring in the trunk. The second group of objects is 40-year-old pine trees that were selected growing in the forest seed orchard. We took the trunk tissue samples on 27 May 2022, 21 June 2022, and 21 July 2022. We have indicated the spatial separation expressed of PsCLE41/44 and PsPXY in pine trunk tissues. PsCLE41/44 was differentially expressed in Fraction 1, including phloem cells and cambial zone. Maximum expression of the PsPXY gene occurred in Fraction 2, including differentiating xylem cells. The maximum expression of the PsCLE41/44 gene occurred on 27 May, when the number of cells in the cambial zone was the highest, and then it decreased to almost zero. The PsPXY gene transcript level increased from May to the end of July. We found that the highest transcript level of the PsWOX4 gene was during the period of active cell ...